Are submissive nurses ethical?: Reflecting on power anorexia - Valeria Lerch Lunardi; Elizabeth Peter; Denise Gastaldo
We believe that the notion of power anorexia, which we define as a lack of desire to exercise power, is central to reflections about nursing ethical concerns. Questioning the assumption that nurses are powerless, we argue that nurses can and do exercise power and that their actions and inactions have consequences not only for themselves, but also for those for whom they care. We propose that a feminist ethics perspective be used both to understand and to overcome nurses' power anorexia. Feminist thinkers remind us not only of oppression's psychological impact, but that stereotypical views about women are socially constructed and, therefore, can be changed. Nurses using this framework should explore the implications of a centralized notion of caring to the way we conceive of power relations in health care. Perhaps deconstructing caring by focusing on how nurses exercise power could help us to re-conceptualize nursing and promote new agendas for health and health care.